Evaluacion de quince materiales de habichuela voluble (Phaseolus vulgaris L.) en cuatro localidades de Caldas - Hincapie, G.E.; Tabares, M.E. (International Center for Tropical Agriculture, 1987)
Fourteen climbing snap bean materials and the check var. Blue Lake were evaluated for yield, plant cycle, days to flowering, strength, fiber content, pod length, efficiency as snap bean, and no. of grains/pod, in 4 sites in Caldas (La Selva, Tesorito, La Libertad, and Montelindo), Colombia. The highest yields were obtained with lines Hab 208, Hab 210, and Hab 221. Var. Blue Lake and line Hab 213 were the most susceptible to phytosanitary problems. (CIAT)